ANALISIS MITIGASI BENCANA BANJIR DI KOTA TANGERANG SELATAN - Muhamad Taslim; Ahmad Jamil Pasaribu; Azhari Aziz Samudra (Media Bina Ilmiah, 2024)
Safe and disaster-resistant residential areas are an urgent need to reduce disaster risk. The role of the government, especially the South Tangerang City Regional Disaster Management Agency (BPBD), is very important in increasing community preparedness in a comprehensive and targeted manner. In this research, we used a qualitative method by utilizing the study literature scheme as a secondary and primary data source obtained from Scopus, Google Scholar, books, performance reports and annual final reports. Our research results show that South Tangerang City has adopted various measures to reduce disaster risk, especially through disaster risk reduction information. The government has implemented mitigation efforts, such as disaster simulations and disseminating mitigation messages through mass media and social media. Apart from that, the government is also making other persuasive efforts to change people's mindsets in realizing a culture of safety, including through habituation and increasing preparedness in disaster prevention. In this context, residential areas that dominate the spatial layout and have different facilities are the main focus. Risk zoning can be done to divide residential areas into zones with different levels of disaster risk, thereby enabling appropriate spatial planning. Early warning infrastructure also needs to be installed to provide residents with information about impending disasters and allow sufficient time to take necessary actions. Clear and well-identified evacuation routes should be provided, while green open spaces can act as "protection zones" and gathering places during evacuation. Apart from that, disaster-resistant buildings need to be considered in planning this residential area. An effective drainage system is also important to reduce the risk of flooding. Public education and awareness about disaster risks as well as regular preparedness training need to be carried out. The government needs to monitor and evaluate the mitigation measures implemented to ensure their effectiveness. Overall, this research underlines the important role of the government and BPBD South Tangerang City in reducing disaster risk in residential areas. By combining comprehensive mitigation measures and involving active community participation, it is hoped that a safety culture can be created that can increase preparedness in facing disasters